The Impact of National Citation Indexes in the Research Evaluation Process - Yavrukova, Bilyana; Milanova, Milena; Lozanova - Belcheva, Elitsa (Qualitative and Quantitative Methods in Libraries, 2020)
The purpose of this paper is to outline the problems connected with the research evaluation process in Bulgaria and the lack of an integrated national database for all scientific disciplines. The authors discussed the changes in the Law for the development of academic staff in the Republic of Bulgaria and evaluation of the quality of scientific activities. The problem concerns the publications of researchers who write on local topics and/or on Bulgarian especially in Social Sciences and Humanities are not well presented in international nor in a national scientometric database is also in focus. The paper presents the scientific project “Design and Development of a Prototype of the Information System „Citation Index of Publications by Bulgarian Authors (Social Sciences)” connected with the summarized problems.